Dinamika Kurikulum Pondok Pesantren Tahfiz Al-Qur′An di Kalimantan Selatan - Rasyidi, Ahyar (el Buhuth: Borneo Journal of Islamic Studies, 2023)
The education system at the tahfiz Islamic boarding school is the same as the Islamic boarding school education system in general, namely there is a curriculum, learning methods, places of study and so on, it's just that there are differences from one hut to another so that it has its own uniqueness in observing it. This study aims to explain and analyze the Tahfiz Al-Qur'an Islamic Boarding School Curriculum in South Kalimantan. The method in this research is descriptive qualitative. There are several tahfiz Islamic boarding schools in South Kalimantan which are the research locations. The findings in this study are that the curriculum in each typology (model) of the Tahfiz Al-Qur'an pesantren has differences. Even within one typology there are some minor differences in the curriculum implemented by the Tahfiz Al-Qur'an pesantren. However, the similarity in the elements of implementing tahfiz Al-Qur'an education makes it found that differences in one typology or model of Islamic boarding school become very minor. In the first typology (model A), the tahfiz Al-Qur'an pesantren curriculum is formulated to support the main program, namely memorizing 30 chapters of the Al-Qur'an. While tahfiz Al-Qurʹan Islamic boarding schools are in model B, it is found that the Al-Qurʹan educational curriculum allocates more time for the tahfiz Al-Qurʹan program, in addition to implementing the existing formal curriculum from the ministry of religion at the Madrasah Tsanawiyah (MTs) and and Madrasah Aliyah (MA).